Pengaruh Pemberian Kombinasi Nutrisi NPK dengan PSB terhadap Pertumbuhan dan Hasil Cabai Merah (Capsicum annuum L.) di Polybag - Saripi, Saripi; Mawardi, Mawardi (JURNAL AGROPLANT, 2025)
The aim of this research was to determine the effect of providing photosynthetic bacteria with NPK pearl fertilizer on the growth and yield of large red chili plants. This research was carried out in Paluombo Hamlet, Sumbersalak Village, Ledokombo District, Jember Regency from mid-January to March 2024 at an altitude of 801 meters above sea level. This study used a non-factorial randomized block design (RAK) with 6 treatments and 6 replications. The treatments are P0 = Control; P1= NPK 25 gr/plant; P2= NPK 15 g/plant and PSB 15 ml/L; P3 = NPK 20 g/plant and PSB 10 ml/L; P4 = NPK 25 g/plant and PSB 5 ml/L; P5 = NPK 10 g/plant and PSB 20 ml/L. Observation data is analyzed using the F test (Data Analysis). If there are significant differences, it will be continued with the LSD (Last Significant Difference) test at the 5% level. The results showed that the treatment of NPK pearl fertilizer with PSB did not have a real effect on all observation parameters, however, the treatment of NPK fertilizer 20 g/plant with PSB 10 ml/L showed the highest average results in observing the number of branches, number of fruit branches and fruit weight.